The Impact of Stressful Life Events on Suicidal Ideation in Gender Dysphoria: A Moderator Effect of Perceived Social Support - Guzmán-Parra, José; Sánchez-Álvarez, Nicolás; Guzik, Justyna; Bergero-Miguel, Trinidad; De Diego‑Otero, Yolanda; Pérez-Costillas, Lucía María (My University, 2023)
Factors associated with suicidal ideation in the gender dysphoria population are not completely understood. This high-risk population is more likely to suffer stressful events such as assault or employment discrimination. This study aimed to determine the association of stressful events and social support on suicidal ideation in gender dysphoria and to analyze the moderator effect of social support in relation to stressful events and suicidal ideation. A cross-sectional design was used in a clinical sample attending a public gender identity unit in Spain that consisted of 204 individuals (51.7% birth-assigned males and 48.3% birth-assigned females), aged between 13 and 59 (M = 27.95 years, SD = 9.58). A Structured Clinical Interview, a list of 16 stressful events, and a functional social support questionnaire (Duke-UNC-11) were used during the initial visits to the unit. The data were collected between 2011 and 2012. A total of 50.1% of the sample have had suicidal ideation. The following stressful events were associated with suicidal ideation: homelessness, eviction from home, and having suffered from physical or verbal aggression. Also, there was an inverse relation between perceived social support and suicidal ideation. There was a statistically significant interaction between a specific stressful event (eviction) and perceived social support. The study suggests that the promotion of safer environments could be related to lower suicidal ideation and that networks that provide social support could buffer the association between specific stressful events and suicidal ideation.
Keywords: Transexualismo; Identidad sexual; Suicidio; Suicide; Transsexualism; Gender identity